Upaya Meningkatkan Kedisiplinan Siswa melalui Layanan Bimbingan Kelompok - Hilyati Fadhilah; Syahniar Syahniar; Megaiswari Biran Asnah (JPGI (Jurnal Penelitian Guru Indonesia), 2019)
Discipline is one of the keys to a person's success, especially a student. If students are disciplined in learning, students will get good learning outcomes. Due to the development of the era in this global era, many students have begun to decrease their discipline in learning because many students have used smartphones, internet cafes and social gatherings. Therefore, it is hoped that through group guidance services can improve student learning discipline